2019
DOI: 10.1073/pnas.1817221116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism for NLRP6 inflammasome assembly and activation

Abstract: Inflammasomes are multi‐protein complexes that detect infectious microbes and cellular stressors, and that activate inflammatory caspases for cytokine maturation and pyroptosis. NLRP6, a sensor protein in the nucleotide‐binding domain (NBD) and leucine‐rich repeat (LRR)containing (NLR) family, is shown to play multiple roles in regulation of inflammation and other innate immune signaling pathways. However, little is known about the molecular mechanism of NLRP6 inflammasome assembly and activation. Using cryo‐E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 41 publications
8
101
3
Order By: Relevance
“…In a human embryonic kidney cell line, overexpressed NLRP6 has been shown to co‐precipitate with overexpressed caspase‐1 and ASC (Levy et al, ). Similarly, the pyrin domain of NLRP6 has been shown to interact with ASC in a purified protein system (Shen et al, ), whereas a recent study in myeloid cells argues that NLRP6 forms a heterogenous inflammasome with ASC, caspase‐1, and caspase‐11, which responds to lipoteichoic acid, a major constituent of the Gram‐positive bacterial cell wall (Hara et al, ; Figure ). Whether lipoteichoic acid stimulates NLRP6 in IECs remains to be determined.…”
Section: A General Overview Of Inflammasomesmentioning
confidence: 99%
“…In a human embryonic kidney cell line, overexpressed NLRP6 has been shown to co‐precipitate with overexpressed caspase‐1 and ASC (Levy et al, ). Similarly, the pyrin domain of NLRP6 has been shown to interact with ASC in a purified protein system (Shen et al, ), whereas a recent study in myeloid cells argues that NLRP6 forms a heterogenous inflammasome with ASC, caspase‐1, and caspase‐11, which responds to lipoteichoic acid, a major constituent of the Gram‐positive bacterial cell wall (Hara et al, ; Figure ). Whether lipoteichoic acid stimulates NLRP6 in IECs remains to be determined.…”
Section: A General Overview Of Inflammasomesmentioning
confidence: 99%
“…Activated caspase-1 is responsible for maturation of pro-IL-1β and pro-IL-18, as well as gasdermin-D-mediated pyroptosis. 24 Recently, the detailed filamentous and crystal structure of the NLRP6 PYD was reported by Shen et al 25 using biochemical and biophysical methods. In addition, the authors have identified the surface that NLRP6 pyrin filament uses to recruit PYD of ASC through molecular dynamics simulations.…”
Section: Mechanism Of Nlrp6 Inflammasome Activationmentioning
confidence: 99%
“…Compared to AIM2 PYD , the α2-α3 loop of NLRP6 PYD is longer, suggesting that NLRP6 PYD permits more degrees of conformational change during filament formation than does AIM2 PYD . 25,26 Both NLRP6 and NLRP3 share similar molecular structures with slight differences in the PYD component. However, while NLRP6 PYD is capable of nucleating ASC PYD by itself, NLRP3 PYD is not able to provide a sufficient platform for ASC assembly.…”
Section: Mechanism Of Nlrp6 Inflammasome Activationmentioning
confidence: 99%
“…To the best of our knowledge, this is the 6 first time such a 'two-layer' architecture has been observed for a FIIND-containing inflammasome sensor. It is remarkably reminiscent of activated NLRC4 and NLRP6 20,21 , where the nucleotide-binding domain (NBD) pre-oligomerizes to bring the CARD or PYRIN domains into close proximity. Furthermore, the observed dimensions of the inner core filament is consistent with those of the recombinant filaments composed of CARD alone ( Fig.S1b, 8 nm in diameter, see below).…”
Section: Nlrp1-card Oligomerization and Dramatically Lowers Its Thresmentioning
confidence: 99%